The use of MFA indicators in the characterization of the settlement sustainability - Karcagi-Kováts, Andrea (Acta Agraria Debreceniensis, 2009)
One of the key sustainability challenges for the coming decades will be to improve the management of natural resources in order to reduce current levels of anthropogenic environmental pressure and respect the biological and physical limits and the carrying capacity of the planet. The first step towards meeting this challenge is an enhancement of the understanding of the material basis of our society. In the past 15 years, scientists in several research institutes have created a fast growing field of research, a new family of different methods, named material flow analysis (MFA). These instruments have an increasing policy relevance: international organizations (UN, EU, OECD) have encouraged member states to establish MFA accounting in their statistical programmes and urged governments and economic actors to use these tools. In this paper I present selected examples to reveal how the MFA approach and derived material flow indicators can be used for the evaluation of sustainability policies at municipality level.